Age and Gender Differences in Trends and Impact of Depression on Quality of Life in the United States, 2008-2016 - Anguzu, Ronald; Nagavally, Sneha; Dawson, Aprill Z.; Walker, Rebekah J.; Egede, Leonard E. (Women's Health Issues, 2021)
We aimed to examine age and gender differences in the relationship between depression and quality of life among United States adults. Medical Expenditure Panel Survey data for 2008 to 2016 on 227,663 adults were analyzed. The dependent variable, quality of life, included physical component summary scores and mental component summary scores from the Short Form Health Survey. The key independent variable, depression, was measured using the two-item Patient Health Questionnaire. General linear regression models examined the relationship between quality of life and depression. Models were adjusted for individual and environmental characteristics, symptom status, functional and biological status, and health perceptions and were stratified by gender and age. In adjusted models, mental component summary scores were significantly lower among those with depression compared with those without depression (β = –0.39; 95% confidence interval [CI], 0.38 to –1.16) and lower among women compared with men (β = –0.10; 95% CI, 0.10 to –1.31). Models stratified by gender and age found women with depression ages 40 to 64 (β = –0.07; 95% CI, 0.07 to –0.20) and 65 or older (β = –0.08; 95% CI, 0.08 to –0.24) had significantly lower physical component summary scores compared with those without depression. Among men with depression, those ages 18 to 39 (β = –0.03; 95% CI, 0.03 to –0.10) and 40 to 64 (β = –0.09, 95% CI, 0.08 to –0.26) had lower physical component summary scores compared with those without depression. Women and men of all ages with depression had significantly lower mental component summary scores compared with those without depression. Public health interventions and clinical approaches to address depression in women and men should target functional status in men and perceptions of health in women.
Keywords: Quality of Life; Age and Gender Differences; Impact of Depression